Active queue management for assured forwarding traffic in differentiated services network / Ng Eng Seong - Ng , Eng Seong (2004)
Congestion control such as RED is needed to maintain network performance level and to allow efficient usage of the network resources. Generally routers use RED to provide better services than using the traditional tail drop mechanism. In brief, RED work by dropping packets probabilistically when the queue start to pile up. Although RED is capable in performing congestion control, enhancement can be done to RED. Current RED is static and the Internet environment has become more demanding and cannot be met with static RED alone. This dilemma is caused by the fact that network has evolved into a very dynamic state and an idea of developing a more dynamic DiffServ with RED has lead towards the creation of the proposed Active Queue Management for DiffServ Traffic (FuzAQM). FuzAQM works by monitoring the condition of the network in real time and is able change its RED parameters based on the congestion level based on fuzzy logic. The main aim of FuzAQM is to improve network throughput and provide means whereby packets can be treated fairly. This is especially true for lower priority packets where these packets are always choke-out by packets of higher priority. In order to demonstrate the feasibility of the idea, FuzAQM is implemented as an extension to the Ns2 network simulator. Simulations results show that the proposed Active Queue Management for DiffServ Traffic improves the total throughput by 0.79% to 6.46% depending on the traffic load. The proposed mechanism is also able to ensure fair treatment of lower priority packets while maintaining relatively high percentage (87%) of throughput for higher priority packets in the network.